KARAKTERISTIK NILAI THE STRENGTH AND DIFFICULTIES QUESTIONNAIRE UNTUK SKRINING KESEHATAN MENTAL PADA ANAK DIDIK BARU DI LEMBAGA PEMBINAAN KHUSUS ANAK DI JAKARTA, INDONESIA: STUDI CROSS-SECTIONAL: Characteristics of the Self-Report Version of the Strengths and Difficulties Questionnaire to Screen Mental Health Problems Among New Juvenile Detainees at the Particular Detention Center for Adolescents in Jakarta, Indonesia: A Cross-Sectional Study - Indry Octavia Trisnawati (Journal of Community Mental Health and Public Policy, 2023)
ABSTRACT Background: Mental health disorders in adolescents can be in the form of emotional and behavioral disorders. Purpose: The study was conducted to determine the characteristics of the Strength and Difficulties Quitionnaire (SDQ) scores in adolescents at LPKA Class II Jakarta. Methods: The study screened of adolescents using the self-report Strength and Difficulties Questionnaire (SDQ), which was given to new juvenile detainees aged <18 year at the Jakayzzrta Detention Center for Children from May to December 2022, totaling 73 people. Data on the age of juvenile detainees, education level, and type of crime were taken through the Correctional Database System. Result: The reliability test using Cronbach's alpha yielded 0.493, and the validity test with pearson bivariate was <0.05. The proportion of those with normal emotional score was 69.9%, the normal conduct score was 80.8%, the normal hyperactivity score was 94.5%, the normal peer score was 58.9%, the normal difficulties score was 75%, and the normal prosocial/strength score was 94.5%. The average age of students was 17 years old (mean±SD: 16.8±1.1), the proportin of junior high school was 55.9% and 36% was involve in physical abuse case. The mental health of new juvenile detainees was in normal condition. Conclusion: Providing SDQ makes it easier to screen mental health in adolescents, especially in special populations such as correctional institutions. The data can illustrate factors that have a major influence on criminal behavior in adolescents. It is necessary to monitor the mental health development of juvenile detainees while in the detention center. ABSTRAKLatar Belakang: Gangguan kesehatan jiwa pada remaja dapat berupa gangguan emosi dan perilaku. Tujuan: Penelitian dilakukan untuk mengetahui karakteristik nilai the Strength and Difficulties Quitionnaire (SDQ) pada remaja di LPKA Kelas II Jakarta. Metode: Studi ini melakukan penapisan pada remaja dengan menggunakan Strength and Difficulties Questionnaire (SDQ) yang diberikan kepada tahanan/narapidana remaja baru (anak didik/andik)berusia <18 tahun di Lembaga Pembinaan Khusus Anak (LPKA) di Jakarta, dari bulan Mei hingga Desember 2022, berjumlah 73 orang. Data usia anak didik, tingkat pendidikan, dan jenis kejahatan diambil melalui Sistem Database Pemasyarakatan. Hasil: Uji reliabilitas dengan Cronbach's alpha adalah 0,493 dan uji validitas dengan bivariat pearson <0,05. Proporsi anak didik dengan status emosional normal adalah 69,9%, perilaku normal adalah 80,8%, hiperaktivitas normal adalah 94,5%, teman sebaya normal adalah 58,9%, kesulitan normal adalah 75%, skor prososial/kekuatan normal adalah 94,5%. Rata-rata usia adalah 17 tahun (mean±SD: 16,8±1,1), tingkat pendidikan SMP 55,9% dan kasus penganiayaan 35,6%. Kesehatan mental anak didik baru dalam kondisi normal. Kesimpulan: Pemberian SDQ memudahkan untuk melakukan skrining kesehatan mental pada remaja terutama pada populasi khusus seperti Lapas. Data tersebut dapat menggambarkan faktor yang memiliki pengaruh besar terhadap perilaku kriminal pada remaja. Pemantauan terhadap perkembangan kesehatan mental tahanan/narapidana remaja selama berada di LPKA perlu dilakukan.